Protein-Protein Interactions as New Drug Targets - Klussmann, Enno.; Klussmann, Enno.; Scott, John.; Scott, John. (Handbook of Experimental Pharmacology,, 2008)
Disease-relevant intracellular protein-protein interactions occurring at defined cellular sites possess great potential as drug targets. They permit highly specific pharmacological interference with defined cellular functions. Drugs targeting such interactions are likely to act with fewer side effects than conventional medication influencing whole cell functions. This book discusses therapeutically relevant protein-protein interactions with a major focus on scaffolding proteins tethering signal transduction processes to defined cellular compartments by direct protein-protein interactions. Recent advances in the development of pharmacological agents interfering with protein-protein interactions are highlighted.